2016
DOI: 10.1111/mmi.13330
|View full text |Cite
|
Sign up to set email alerts
|

The extracytoplasmic function σ factor σC regulates expression of a branched quinol oxidation pathway in Corynebacterium glutamicum

Abstract: Bacteria modify their expression of different terminal oxidases in response to oxygen availability. Corynebacterium glutamicum, a facultative anaerobic bacterium of the phylum Actinobacteria, possesses aa3 -type cytochrome c oxidase and cytochrome bd-type quinol oxidase, the latter of which is induced by oxygen limitation. We report that an extracytoplasmic function σ factor, σ(C) , is responsible for the regulation of this process. Chromatin immunoprecipitation with microarray analysis detected eight σ(C) -bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 146 publications
(195 reference statements)
1
21
0
Order By: Relevance
“…Expression of the genes regulated by σ C has recently been described (Toyoda and Inui 2016a). We selected the promoter of the C. glutamicum ATCC 13032 cg2556 gene encoding an uncharacterized iron-regulated membrane protein (corresponding to the cgR_2208 gene in the sequence of C. glutamicum R; Toyoda and Inui 2016a) to test sigma dependency of its promoter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of the genes regulated by σ C has recently been described (Toyoda and Inui 2016a). We selected the promoter of the C. glutamicum ATCC 13032 cg2556 gene encoding an uncharacterized iron-regulated membrane protein (corresponding to the cgR_2208 gene in the sequence of C. glutamicum R; Toyoda and Inui 2016a) to test sigma dependency of its promoter.…”
Section: Resultsmentioning
confidence: 99%
“…We selected the promoter of the C. glutamicum ATCC 13032 cg2556 gene encoding an uncharacterized iron-regulated membrane protein (corresponding to the cgR_2208 gene in the sequence of C. glutamicum R; Toyoda and Inui 2016a) to test sigma dependency of its promoter. In vitro transcription assays confirmed that cg2556 transcription is σ C -specific (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some C. glutamicum promoters were defined as r M -dependent by some authors [12] whereas as r H -dependent by others [5]. Very recently, a consensus sequence of several promoters of r C -controlled genes was deduced [24]. We report here the evidence of overlap of C. glutamicum sigma factors r A and r B , or r H and r E in recognizing specific promoters, obtained by use of C. glutamicum in vitro transcription system.…”
Section: Introductionmentioning
confidence: 89%